2019
DOI: 10.1186/s12974-019-1581-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of non-macrophage cell-derived HMGB1 in oxaliplatin-induced peripheral neuropathy and its prevention by the thrombin/thrombomodulin system in rodents: negative impact of anticoagulants

Abstract: BackgroundMacrophage-derived high mobility group box 1 (HMGB1), a damage-associated molecular pattern (DAMP) protein, plays a key role in the development of chemotherapy-induced peripheral neuropathy (CIPN) caused by paclitaxel in rodents. Endothelial thrombomodulin (TM) promotes thrombin-induced degradation of HMGB1, and TMα, a recombinant human soluble TM, abolishes peripheral HMGB1-induced allodynia in mice. We thus examined whether HMGB1, particularly derived from macrophages, contributes to oxaliplatin-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 40 publications
6
56
0
Order By: Relevance
“…An additional anti-inflammatory effect of ART-123 attributed to direct binding to high-mobility group box 1 protein (HMGB1) and enhancement of its degradation by thrombin has also been reported [19,20]. Recently, it has been reported that ART-123 prevented oxaliplatin-induced hyperalgesia and allodynia in animal models [21,22]. The animal study suggested that ART-123 prevents the development of sensory symptoms of OIPN through activation of TAFI and protein C without affecting the anti-tumor activity of oxaliplatin [21].…”
Section: Introductionmentioning
confidence: 96%
“…An additional anti-inflammatory effect of ART-123 attributed to direct binding to high-mobility group box 1 protein (HMGB1) and enhancement of its degradation by thrombin has also been reported [19,20]. Recently, it has been reported that ART-123 prevented oxaliplatin-induced hyperalgesia and allodynia in animal models [21,22]. The animal study suggested that ART-123 prevents the development of sensory symptoms of OIPN through activation of TAFI and protein C without affecting the anti-tumor activity of oxaliplatin [21].…”
Section: Introductionmentioning
confidence: 96%
“…HMGB1, a nuclear protein, once released to the extracellular space, plays a role as a damage-associated molecular pattern (DAMP) or alarmin protein, and promotes not only inflammation [4,5], but also pain signals [6]. Extracellular HMGB1 in the peripheral tissue is considered to participate in inflammatory and neuropathic pain through direct or indirect activation of RAGE, Toll-like receptor 4 (TLR4) or CXCR4 [2,[7][8][9][10]. We have demonstrated that the activation of RAGE by HMGB1 derived from unknown cells plays a role in the development of the bladder pain accompanying CPA-induced cystitis in mice [2].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the identification of reliable biomarkers able to predict the clinical course of OIPN would represent a relevant improvement in the clinical research toolkit. Currently, measurement of the level of neurofilament light chains in plasma or serum samples seems to be the most promising candidate based on preclinical evidence obtained using different neurotoxic chemotherapy regimens [55,56], but further validation in the clinical setting is required.…”
Section: Discussionmentioning
confidence: 99%